QS8: Fat Grafting Depletes Profibrotic Prrx1-positive Fibroblasts In Irradiated Skin And Mitigates Radiation-induced Groin Contracture. (July 2021) - Rosealie Borrelli, Mimi; Adem, Sandeep; Griffin, Michelle; Diaz, Nestor; Longaker, Michael T.; Wan, Derrick
Abstract : Purpose: Contracture is a long-term complication of radiotherapy (RT) that results from pathologic fibrosis of soft tissue in the radiation field. Fat grafting can regenerate fibrotic soft tissue by decreasing collagen density and reorganizing collagen fiber networks. Fibroblasts are the predominant cell involved in extracellular matrix (ECM) synthesis, and dermal fibroblasts possess distinct embryonic origins. We recently identified a profibrotic fibroblast in the mouse ventral dermis marked by embryonic expression of paired related homeobox 1 (Prrx1). Here we sought to investigate how fat grafting alters Prrx1-positive subpopulation distribution as well as functional contractures. Methods: Adult Prrx-1 Cre ;R26 mTmG reporter mice (n=9) underwent whole body lethal irradiation with 9 Gy for hematopoietic depletion. Mice were immediately reconstituted with 2 million nucleated bone-derived cells from donor NSG (NOD.CB17- Prkdcs scid /J) mice via retro-orbital sinus injection. The success of reconstitution and immunodepletion was assessed by fluorescence-activated cell sorting (FACS) analysis of peripheral blood. After 4 weeks, 30 Gy was delivered to the right hindlimb in five fractionated doses to generate limb contracture. The irradiated, contracted limb was then grafted with 200 μl fresh human lipoaspirate and limb extension was measured over the subsequent 8 weeks, at which point skin was harvested for assessment of fibroblast subtypes for FACS and immunofluorescence. A group of mice with radiation-induced groin contracture did not undergo fat grafting and served as the control group. Results: FACS analysis indicated successful immunodepletion and engraftment by 3 weeks post bone marrow transplantation. At one month following groin irradiation, mice had developed significant right hind limb contracture with significantly reduced limb extension (****p⩽0.0001). Histologically this was paralleled by thickening of the dermis, and substantial expansion of the fibrogenic Prrx-1-positive fibroblast subpopulation. While human fat graft volume retention was reduced over 8 weeks following implantation, this was associated with significantly improved in limb extension. The skin overlying the grafted fat showed reduced collagen density, as indicated by trichrome staining, as well as a reduction in the fibrogenic Prrx-1-positive fibroblast subpopulation by immunofluorescence imaging, as compared to the control mice. Conclusion: Here we show that fat grafting improves the extensibility of irradiated and contracted hind limbs and reverses radiation-induced skin fibrosis by both reducing the collagen content and by altering the composition of dermal fibroblast subpopulations. Specifically, fat grafting results in a depletion of the Prrx-1-positive fibroblast subpopulation. Further elucidating how this profibrotic fibroblast subpopulation is involved in ventral surface soft tissue fibrosis will facilitate development of novel strategies to treat/prevent debilitating late side-effect of radiotherapy.